Information, pesticide safety behaviors, and perceived pesticide health risks in Maputo and Lusaka - Goeb, Joseph C.; Smart, Jenny; Snyder, Jason E; Tschirley, David (Agricultural and Applied Economics Association, 2019)
To increased pesticide use in Sub-Saharan Africa (SSA) brings new health and safety risks to smallholder farmers; Farmers in developing countries seldom use complete personal protective equipment (PPE) when handling and applying pesticides, which often leaves them highly exposed to toxic chemicals; The high potential for exposure leads to large acute illness risks from pesticide use; Researchers agree that improved and targeted extension and training efforts are needed to ensure that farmers use pesticides safely; however literature has not explored in detail the relationships between agriculture information channels and perceived pesticide health risks and safety behaviors.